Construction, Enzyme Response, and Substrate Capacity of a Hyaluronan–Cyclodextrin Supramolecular Assembly. Issue 4 (10th December 2015) - Hu, Ping; Chen, Yong; Li, Jing‐Jing; Liu, Yu
Abstract: A supramolecular assembly was constructed with a cationic cyclodextrin (EICD) and native hyaluronan (HA). The cationic carboxylic ester pendants on HA support hyaluronidase (HAase)‐responsive sites and the EICD supports artificial carboxylic esterase responsive sites. Substrate‐binding models were investigated by using environment‐sensitive fluorescence probes 2‐ p ‐toluidino‐6‐naphthalenesulfoniate sodium (2, 6‐TNS) and thioflavin T (ThT). On a HA/EICD assembly, EICD was able to bind an anionic substrate and HA and EICD constructed the cationic substrate binding site together. This assembly could be used as a sequential dual‐substrate carrier. Abstract : Get it together : A supramolecular assembly that exhibited a HAase/esterase response was constructed with a cationic cyclodextrin (EICD) and native hyaluronan (HA). Owing to these components having two different types of binding sites, the assemblies can bind both cationic and anionic substrates.